Prognostic nutritional index is a better inflammation based prognostic marker in elderly patients with hepatocellular carcinoma after surgery - Qionglan Wu; Jinhua Zeng; Jianxing Zeng (Scientific Reports)
Abstract The role of inflammation-related markers in patients with elderly hepatocellular carcinoma (HCC) is not well known. This study aimed to evaluate and compare the prognostic value of various inflammation-related markers in elderly HCC patients after radical resection.350 elderly HCC patients after radical resection were included. Survival rate and prognostic analysis were using Kaplan-Meier and Cox regression analysis. The prognostic value of inflammation-related markers was compared by C-index and time-dependent receiver operating characteristic curve (AUC). Propensity score matching (PSM) was used for patient selection to minimize bias. The C-index and time-dependent AUC showed that PNI was higher than the other inflammation-related markers. After PSM, the 1-year, 3-year, and 5-year overall survival rates in the low prognostic nutritional index (PNI) and high PNI groups were 83.3%, 69.5%, 51.5%, and 95.0%, 87.8%, 71.3% (p = 0.047), respectively. The 1-year, 3-year, and 5-year recurrence-free survival rates in the two groups were 63.3%, 47.8%, 24.5%, and 86.7%, 76.3%, 57.1% (p < 0.001), respectively. Multivariate Cox regression revealed that PNI was the independent risk factor associated with death (p = 0.016, HR = 0.552) and tumor recurrence (p = 0.001, HR = 0.432). PNI was a better inflammation-based prognostic marker in elderly HCC patients after radical resection. This simple marker could help physicians determine elder HCC patients at high risk of tumor recurrence for frequent clinical surveillance.